Analysis of anthropometric data for designing corsetryproducts of bra group - Лєсовець, Олена Володимирівна (Technology audit and production reserves, 2014)
This article provides an analytical overview of typical figures classifications for designing corsetry products used by the leading foreign trade companies and manufacturers, as well as their comparison with the national standards. As a result, it was concluded that the number of proposed size types and bra cup depth of foreign manufacturers is much higher than in the national standards. This is explained by the fact that the manufacturers are interested in attracting a wider range of potential buyers. The size charts of large trading companies in contrast with the size charts grid of smaller enterprises reflect the options of population types and sizes more completely. The analysis of the current national anthropometric database for designing corsetry product of bra group demonstrates out-of-date nature and incompleteness, as well as the need for conducting a measurement survey to review it. The anthropometric study aimed at the analysis of designing corsetry products of bra group, in which 350 women took part, shows the necessity of introducing two new extra small sizes and one extra big size into the anthropometric database. It also reveals a number of dependencies which demonstrate the changes in individual parameters of the female body depending on age, profession, body fat and posture.